Variables and NEPSE Index - Pandey, Netra Kumar (Bhairahawa Campus Journal, 2023)
In the context of Nepal, this study investigates the long- and short-term factors that affect inflation with monthly time series data of fiscal year 2016/17 to 2021/22 (70 observations) employing the ARDL bounds test and error correction technique of econometric analysis. In order to identify the order of integration, the stationary of all variables were investigated by running PP test. Variables are found to be stationary at level I (0) and first I (1) difference. In this study NEPSE Index (NI) is the dependent variable and Interest Rate (IR), Broad Money Supply (MS), Exchange Rate (ER) and Inflation (INF) are the independent variables. The study shown that Exchange rate(ER), Interest Rate(IR) Broad Money Supply (MS) and is must significant with NEPSE Index (NI). Where as there is insignificant relationship between NEPSE Index (NI) and Inflation (INF) in short run. These results imply that the short-term success of Nepal's Stock market strategy depends on managing interest rate, exchange rate and reducing imports from India, increasing foreign reserve and consistent political scenario as well.